ЦЕЛИ НАКАЗАНИЯ ПРИ ПОЖИЗНЕННОМ ЛИШЕНИИ СВОБОДЫ (Journal of actual problems of jurisprudence, 2019)
This article discusses the objectives in imposing the penalty of life imprisonment or problems in its implementation.